2022
DOI: 10.1101/2022.01.12.22269023
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Extremely potent monoclonal antibodies neutralize Omicron and other SARS-CoV-2 variants

Abstract: The ongoing coronavirus disease 2019 (COVID-19) pandemic, caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), has triggered a devastating global health, social and economic crisis. The RNA nature and broad circulation of this virus facilitate the accumulation of mutations, leading to the continuous emergence of variants of concern with increased transmissibility or pathogenicity1. This poses a major challenge to the effectiveness of current vaccines and therapeutic antibodies1,2. Thus, ther… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 57 publications
0
7
0
2
Order By: Relevance
“…Early modelling studies have predicted that the REGN-COV2 (Casirivimab and Imdevimab), as well as the Rockefeller University antibody C135 are still efficacious against the omicron ( Chen et al, 2021a ; Aleem et al, 2022 ). NA8 and NE12 are the prophylactic and therapeutic antibodies that are developed using combinatorial antibody phage-display library methodology, and are effective against Omicron in picomolar concentrations ( Chen et al, 2022 ). Future strategy to combat Omicron requires high potency drugs which could reduce viral replication and spreading, and be effective against all the circulating variants, including any possible variants that could emerge (Fang “Flora” Fang and Shi, 2021 ; Mohiuddin and Kasahara, 2021 ).…”
Section: Therapeutic Advances Against Omicronmentioning
confidence: 99%
“…Early modelling studies have predicted that the REGN-COV2 (Casirivimab and Imdevimab), as well as the Rockefeller University antibody C135 are still efficacious against the omicron ( Chen et al, 2021a ; Aleem et al, 2022 ). NA8 and NE12 are the prophylactic and therapeutic antibodies that are developed using combinatorial antibody phage-display library methodology, and are effective against Omicron in picomolar concentrations ( Chen et al, 2022 ). Future strategy to combat Omicron requires high potency drugs which could reduce viral replication and spreading, and be effective against all the circulating variants, including any possible variants that could emerge (Fang “Flora” Fang and Shi, 2021 ; Mohiuddin and Kasahara, 2021 ).…”
Section: Therapeutic Advances Against Omicronmentioning
confidence: 99%
“…As of February 22, 2022, 31 studies met the search criteria (Figure 1). Twelve of the studies were reported in a peer-reviewed publication [10][11][12][13][14][15][16][17][18][19][20][21]; 19 were published as preprints [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40]. Two additional studies comprised data available on the NIH National Center for Advancing Translational Sciences (NCATS) SARS-CoV-2 Variants and Therapeutics open data portal [41,42].…”
Section: Search Resultsmentioning
confidence: 99%
“…певтическую активность в отношении SARS-CoV-2, включая B.1.351 и B.1.1.529, в то время как клинические исследования не представили убедительных данных в отношении штамма Омикрон [47].…”
Section: лечениеunclassified